Pathopharmacology - Bruce Colbert; Kurtis Pierce (Cengage Learning, 2018)
MindTap Pathopharmacology helps you learn on your terms. TAKES YOU FROM BASIC KNOWLEDGE AND UNDERSTANDING TO HIGHER LEVEL LEARNING USING A LEARNING OBJECTIVES BASED APPROACH. MINDTAP CREATES A UNIQUE LEARNING PATH OF RELEVANT READINGS, MULTIMEDIA, AND ACTIVITIES BY LEARNING OBJECTIVE THAT MOVE YOU UP THE LEARNING TAXONOMY FROM BASIC KNOWLEDGE AND COMPREHENSION TO ANALYSIS AND APPLICATION. INSTANT ACCESS IN YOUR POCKET. Take advantage of the MindTap Mobile App to learn on your terms. Read or listen to textbooks and study with the aid of instructor notifications, flashcards, and practice quizzes. MINDTAP HELPS YOU CREATE YOUR OWN POTENTIAL. GEAR UP FOR ULTIMATE SUCCESS. Track your scores and stay motivated toward your goals. Whether you have more work to do or are ahead of the curve, you'll know where you need to focus your efforts. And the MindTap Green Dot will charge your confidence along the way. MINDTAP HELPS YOU OWN YOUR PROGRESS. MAKE YOUR TEXTBOOK YOURS. No one knows what works for you better than you. Highlight key text, add notes, and create custom flashcards. When it's time to study, everything you've flagged or noted can be gathered into a guide you can organize. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.